2021
DOI: 10.33275/1727-7485.1.2021.664
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation phase transition in austral summer over the Antarctic Peninsula

Abstract: Investigating precipitation phase transitions is crucial for improving our understanding of precipitation formation processes and impacts, particularly in Polar Regions. This study uses observational data and numerical modelling to investigate precipitation phase transitions in the western and northern Antarctic Peninsula (AP) during austral summer. The analysis is based on the ERA5 reanalysis product, dynamically downscaled using the Polar-WRF (Polar Weather Research and Forecasting) model, evaluated using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In our view, the conclusions of Palerme et al (2017) and our previous estimations allow us to have high confidence in our obtained results based on CORDEX RCMs driven by CMIP5, notwithstanding we analyzed only the liquid share of total precipitation. There was an increase of such liquid precipitation in the AP region in previous warm events (e. g., Chyhareva et al, 2021;Wille et al, 2022) and expected with future warming based on an ensemble of the next-generation CMIP6 models (Vignon et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our view, the conclusions of Palerme et al (2017) and our previous estimations allow us to have high confidence in our obtained results based on CORDEX RCMs driven by CMIP5, notwithstanding we analyzed only the liquid share of total precipitation. There was an increase of such liquid precipitation in the AP region in previous warm events (e. g., Chyhareva et al, 2021;Wille et al, 2022) and expected with future warming based on an ensemble of the next-generation CMIP6 models (Vignon et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…It is shown that combining clouds with liquid precipitation could enhance melting events by hindering freezing processes (Van Tricht et al, 2016). On the other hand, phase transition of precipitation on the ground is still a big challenge for predicting and needs more focused research with simulation and measurements as were recently studied with ERA5 reanalysis product downscaled by Po lar-WRF model and additional measurements at Aka demik Vernadsky (hereinafter Vernadsky) and Escu dero stations (Chyhareva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the modeling resolution should be increased. Although, Chyhareva et al (2021) showed that the Polar WRF model has good applicability in the simulation of the precipitation phase transitions for this region.…”
Section: Discussionmentioning
confidence: 96%
“…Two surface melting events that were triggered by the combined impact of ARs and foehn warming are studied, occurring on the northern AP in December 2018 and February 2022. In December 2018, a high precipitation amount (up to 5.7 mm/day) was observed at Vernadsky (Chyhareva et al, 2021), and surface melting also detected on the leeside based on National Snow and Ice Data Center (NSIDC) daily surface melt extent (not shown). At the beginning of January 2022, a large expanse of sea ice (about 2,000 km 2 ), which had persisted in the Larsen B embayment since 2011 and that can bond to and stabilize the ice shelves, began to break up between 17 and 19 January 2022 (acquired by MODIS on NASA's Terra and Aqua satellites).…”
Section: December 2018 and February 2022 Surface Melt Events Over The...mentioning
confidence: 99%